Decentralized activity centers in rural Bangladesh: A step towards effective emergency situation management in the post-pandemic cities - Anutosh Das; Sumita Roy; Mohammad Shahriyar Parvez; Musleh Uddin Hasan (Journal of Urban Management, 2021)
The concentrated development in the urban areas attracts people to migrate into cities for a better living and consequently leading towards the root causes of many socio-economic and environmental nuisances. Moreover, the high-density urban living engines the rapid spread of contagious diseases and thereby threatening the lives of millions of people. The high death rate and affected cases of COVID-19 in Dhaka City, Bangladesh, and its nearby areas, i.e., Gazipur and Narayanganj, gives a clear indication of the importance of activity center decentralization. Due to the growing demand for healthcare, it has become necessary to decentralize the health care facilities to the remote areas and the Government of Bangladesh has already adopted some key measures. In this context, this particular research has tried to determine the mutilated amenity facilities for diversified stakeholders aiming parallel discouragement of the out-migration of skilled professionals and attracting the non-local professionals to live in rural Bangladesh. The research critically argues that if proper facilities can be provided in rural areas, rural to urban migration can be demotivated. It also argues that the development of small urban activity centers will help emergency situation management. The methodology includes an amalgam of a two-step exploratory and descriptive survey prior to and during the global COVID-19 outbreak. The determinants and precedence of required services were determined by Focus Group Discussion (FGD), structured direct questionnaire surveys, secondary online questionnaire surveys and persona approach. The outcome of the research proposes a glimpse of management measures for Bangladesh to tackle future pandemic situation which could be a role model for developing cities also.
Keywords: 710; COVID-19 pandemic; Emergency management; Decentralization; Post-pandemic city; Activity center development